A holistic approach to managing a patient with heart failure. (March 2013) - Duncan, Alison; Cunnington, Colin
Despite varied and complex therapeutic strategies for managing patients with heart failure, the prognosis may remain poor in certain groups. Recognition that patients with heart failure frequently require input from many care groups formed the basis of The British Society of Heart Failure Annual Autumn Meeting in London (UK), in November 2012, entitled: 'Heart failure: a multidisciplinary approach'. Experts in cardiology, cardiac surgery, general practice, care of the elderly, palliative care and cardiac imaging shared their knowledge and expertise. The 2-day symposium was attended by over 500 participants from the UK, Europe and North America, and hosted physicians, nurses, scientists, trainees and representatives from the industry, as well as patient and community groups. The symposium, accredited by the Royal College of Physicians and the Royal College of Nursing, focused on the multidisciplinary approach to heart failure, in particular, current therapeutic advances, cardiac remodeling, palliative care, atrial fibrillation, heart rate-lowering therapies, management of acute heart failure and the management of patients with mitral regurgitation and heart failure.